Analysis of lymphocyte profile in lymph nodes, bronchoalveolar lavage fluid and peripheral blood in patients with stage II sarcoidosis. (December 2022) - Mi, Song; Cui, Na; Feng, Xiaokai; Jiang, Chunguo; Huang, Kewu; Zhang, Liming
Abstract: Objective: To evaluate the lymphocyte profile (LP) in lymph node puncture fluid (LNPF) of mediastinal and hilar lymph nodes, bronchoalveolar lavage fluid (BALF), and peripheral blood (PB) involved in stage 2 sarcoidosis. Methods: After selection, 31 patients diagnosed with stage II sarcoidosis were finally included. Patients were further divided into symptomatic (n = 17) and asymptomatic (n = 14) groups according to the presence or absence of respiratory symptoms. The LP in lymph node puncture fluid (LNPF), bronchoalveolar lavage fluid (BALF), and peripheral blood (PB) were evaluated and compared using flow cytometry. The relationship between respiratory symptoms and LP was preliminarily analyzed. Results: The proportions of T cells and CD4 T cells, and CD4/CD8 ratio in BALF were significantly higher than that of LNPF with PB (all P < 0.05). The proportions of lymphocyte cells, CD8 T cells, NK cells, and CD4/CD8 ratio in LNPF and PB were significantly different (all P < 0.05). There were significant differences in CD4 T cells [72.40 (68.90, 75.55) vs.46.30 (38.55, 52.50), P = 0.004], CD8 T cells (9.9 ± 3.9 vs. 16.8 ± 6.8, P = 0.002), and CD4/CD8 ratio (7.9 ± 2.8 vs. 3.9 ± 1.5, P < 0.001) in BALF between the symptomatic group and asymptomatic group (all P < 0.05). The T cells (rs = 0.447, P = 0.011), CD4 (rs = 0.572, P = 0.002), and CD4/CD8 ratio (rs = 0.701, P < 0.001) in BALF were positively correlated with respiratory symptoms. Conclusion: The LP in LNPF, BALF and PB were significantly different and the main index correlated with respiratory symptoms was CD4/CD8 ratio in BALF. The difference of LP in BALF and LNPF may help to deeply understand the pathophysiological process and may reflect the different degree of lung and lymph node lesion. Highlights: LP in mediastinal and hilar lymph nodes involved in stage 2 sarcoidosis. The LP in LNPF, BALF and PB were significantly different. The main index correlated with respiratory symptoms was CD4/CD8 ratio in BALF. The authors declare there is no conflict of interest existed in this study.